Board Size Moderates the Influence of Research and Development (R&D) Intensity on Financial Performance - Oktriasih, Charisma (UMSurabaya Publishing, 2024)
Innovation and R&D activities have been highlighted as important factors influencing corporate growth strategies and corporate financial performance. However, the company’s management policy determines the decision to invest in R&D activities, and the board of directors is the leading company’s manager. This research examines the effect of R&D intensity on company financial performance, with board size as a moderating variable. This research uses multiple linear regression methods, ordinary least squares (OLS) and moderated regression analysis (MRA) with the application program IBM SPSS Statistics 22 for Windows to explore the hypothesis. The results of this paper show that R&D intensity has a positive and insignificant effect on corporate financial performance. Then, after board size was entered into the regression model, the results showed that board size positively and significantly moderated the influence of R&D intensity on the company’s financial performance